Prevalence of faecal incontinence among a healthy population in a tertiary referral center in Ireland - Colin Sirr (Shiraz University of Medical Sciences, 2019)
Background: Faecal incontinence (FI) is a debilitating condition associated with social isolation and poor quality of life. The prevalence of FI within the Irish setting has yet to be fully elucidated. The aim of the current study was to provide insights into the prevalence of FI among the population of the West of Ireland.Method: An anonymized questionnaire-based survey was conducted between May and August 2018 in a tertiary referral centre. Staff members and patients above the age of 18yrs were invited to take part in the study. The Rome IV criteria for FI was utilized. Data collected included patient demographics, co-morbidities, FI risk factors, surgical and obstetric history. Severity of faecal incontinence was assessed using the Wexner Continence Scale (WCS). Results: A total of 200 participants (F/M 124/76, median age 47yrs (18-86yrs)) were enrolled into the study. The overall prevalence of FI was 31.5% (63/200). 81 (40.5%) experienced some form of bowel dysfunction in the past. Of the 81, only 45 (55.5%) had discussed their FI symptoms with a healthcare professional. The FI group had 14 individuals (7%) with severe incontinence (Wexner score ≥ 9), 18 (9%) reported moderate incontinence (Wexner 5-8) and 31 (16%) reported mild incontinence (Wexner score 1-4). The FI cohort had a significantly greater incidence of inflammatory bowel disease, irritable bowel syndrome and previous bowel surgery (p